Hemianomalous pulmonary venous drainage and type IIb coronary sinus septal defect – Utility of subxiphoid and right parasternal views. Issue 10 (23rd September 2021) - Gopalakrishnan, Arun; Menon, Sabarinath; Sasikumar, Deepa; Kurup, Harikrishnan K. N.; Krishnamoorthy, Kavassery Mahadevan
Abstract: A 3‐year‐old boy presented with history of recurrent respiratory tract infections in infancy. Clinically he had hemodynamically significant pre‐tricuspid left‐to‐right shunt and no pulmonary hypertension. Transthoracic echocardiography delineated anomalous drainage of the left sided pulmonary veins to a dilated coronary sinus opening into the right atrium. Closer evaluation from the subxiphoid and right parasternal views led to the diagnosis of an associated type IIb coronary sinus septal defect.